A longitudinal study of self-control at the transition to secondary school: Considering the role of pubertal status and parenting. (July 2016) - Ng-Knight, Terry; Shelton, Katherine H.; Riglin, Lucy; McManus, I.C.; Frederickson, Norah; Rice, Frances
Abstract: Higher self-control in children and adolescents is associated with a range of positive outcomes in adulthood. However, little is known about the naturalistic development of self-control during early adolescence and the factors that affect this. We examined the role of puberty and parenting style as theoretically important influences on stability and change in self-control. A longitudinal (3 waves), multiple-informant dataset of children entering early adolescence ( M = 11 years) was used to explore longitudinal change in self-control using latent growth curve modelling. Children's self-control declined during the one-year study period and declines were associated with children's behavioural and social functioning. Associations with self-control were found for pubertal status and parental warmth and hostility, but not for parental discipline. The findings suggest that during early adolescence, when children make the transition to secondary school, self-control declines. This is particularly the case for those experiencing puberty earlier than their peers. Parent warmth influences the trajectory of self-control during this period.